2016
DOI: 10.1212/wnl.0000000000003101
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic bacterial meningitis in human adults

Abstract: Zoonotic bacterial meningitis is uncommon but is associated with specific complications. The suspicion should be raised in patients with bacterial meningitis who have recreational or professional contact with animals and in patients living in regions endemic for specific zoonotic pathogens. An immunocompromised state is associated with a worse prognosis. Identification of risk factors and underlying disease is necessary to improve treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Local C. Canimorsus infection may be underdiagnosed because of the administration of effective empiric antibiotics. Giving the fact that postexposure antibiotic prophylaxis is commonly prescribed after a dog's bite, this may lead to negative CSF cultures and underestimation of the incidence of this zoonotic disease …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local C. Canimorsus infection may be underdiagnosed because of the administration of effective empiric antibiotics. Giving the fact that postexposure antibiotic prophylaxis is commonly prescribed after a dog's bite, this may lead to negative CSF cultures and underestimation of the incidence of this zoonotic disease …”
Section: Discussionmentioning
confidence: 99%
“…These first‐line antibiotics are usually efficient against zoonotic pathogens. However, reduced susceptibility of C. canimorsus for trimethoprim/sulfamethoxazole and gentamicin has been described . Several studies have shown clindamycin to be the most active agent against Capnocytophaga spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection has also been reported following non-traumatic contact, including kissing and being licked by animals and the pathogen has also been isolated in cases where no animal contact has occurred 3–6 . P multocida meningitis is most frequently reported in infants; it is a very rare cause of adult bacterial meningitis; a recent review article counted only 36 adult cases reported worldwide 7. Disseminated infection has more often been reported in those with predisposing factors such as advanced age, immune compromise, cirrhosis, renal replacement therapy or recent neurosurgical intervention 8.…”
Section: Discussionmentioning
confidence: 99%
“…P multocida is usually sensitive to third-generation cepahalosporins,7 which is recommended as first-line empirical therapy for presumed bacterial meningitis in most UK hospital guidelines. Most, but not all, isolates are sensitive to penicillin and ampicillin,11–13 and therapy can therefore be rationalised with antibiotic susceptibility patterns.…”
Section: Discussionmentioning
confidence: 99%